Are We Retiring too Early? - Pierre Pestieau (Center for Economic Studies and ifo Institute (CESifo), 2001)
The European population is living longer but retiring earlier. More and more individuals are spending an increasing fraction of their life-time relying on retirement benefits. At the same time, social security programs face mounting financial difficulties. The purpose of this paper is to explain why people are retiring so young and why it is so difficult to reverse a trend that could turn out to be fatal to social security systems that have worked so well up to now.To define the second-best retirement age as well as to explain why reasonable reforms are difficult, if not impossible, we use the tools of optimal income tax theory and of political economy.
Keywords: 330